THE EFFECTIVENESS OF DISCOVERY LEARNING MODEL TO IMPROVE ELEMENTARY STUDENTS’ CRITICAL THINKING SKILLS AND SELF-EFFICACY - Ana Mufidatus Saadah; Haryono Haryono; Tri Joko Raharjo (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Class V students in Kayen District, Pati Regency, are still using expository methods of learning at SD Negeri. Learning outcomes for students are still below the KKM because the teaching methodology is less innovative, students' critical thinking abilities and self-efficacy are low, and students are not very engaged in the learning process. The percentage of pupils whose test scores were below the KKM was calculated from the available data and was found to be 70.21% based on the initial documentation activity. The purpose of this research is to find out if teaching using the discovery learning approach at public elementary schools in the Kayen District of the Pati Regency raises students' critical thinking and sense of agency. The study employs a non-equivalent pre- and post-test within-control group design, which is a type of quasi-experimental methodology. In total, 48 students participated in the study, with 26 participating in the experimental class and 22 participating in the control class. Methods of data gathering include standardised tests, non-tests in the form of rated questionnaires, and record keeping. Descriptive analysis, a precondition test, and a hypothesis test (including the N-Gain and the average difference tests) are used to examine the data. An efficacy value of 1.7903 was found between the experimental group's N-Gain for critical thinking skills and the control group's N-Gain for TKBK. When the experimental group's N-Gain self-efficacy score was compared to the control group's, an efficiency value of 1.4253 was calculated. With an efficacy rating greater than 1, it's clear that the discovery learning paradigm helps students develop their critical thinking and sense of agency. Therefore, it is recommended that educators employ the discovery learning paradigm in the classroom so that students are more engaged and invested in their education.